1994
DOI: 10.2166/wst.1994.0762
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aerated biofiltration at industrial scale

Abstract: Experience with biofilters, acquired over many years, has made it possible to control their operating parameters. The goal of this article is to present an assessment of operational biofilters, in particular their air consumptions, their sludge productions, their energy balances as well as the duration of their filtration cycles. Some tests, carried out on medium to large full scale units, are described at the same time as the process results. These experiences in the design and operation of biofilters led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The sludge specific production value and the other parameters characterizing in period A the SBBR during the interval between two washing steps are reported in Table 6. The SSP value reported in this table (i.e., 0.1 kg VSS/ kgCODremoved) is much lower than those commonly reported for continuous biofilm reactors usually falling in the range 0.3-0.5 kgVSS/kgCODremoved (35)(36)(37)(38). Such a rather low production of sludge resulted substantially the same throughout the whole experimentation and was confirmed by the measured very low phosphorus consumption (1.7 gPO4-P/ kgCODremoved).…”
Section: Resultssupporting
confidence: 64%
“…The sludge specific production value and the other parameters characterizing in period A the SBBR during the interval between two washing steps are reported in Table 6. The SSP value reported in this table (i.e., 0.1 kg VSS/ kgCODremoved) is much lower than those commonly reported for continuous biofilm reactors usually falling in the range 0.3-0.5 kgVSS/kgCODremoved (35)(36)(37)(38). Such a rather low production of sludge resulted substantially the same throughout the whole experimentation and was confirmed by the measured very low phosphorus consumption (1.7 gPO4-P/ kgCODremoved).…”
Section: Resultssupporting
confidence: 64%
“…Evaluation campaigns carried out in French treatment plants showed that the highest energy consumption is due to aeration, which consumes on average 87% of the energy related to secondary treatment (Canler and Perret, 1993). The energy balance undertaken by Kleiber et al (1993) in the Perpignan treatment plant (France), covering a period of 12 months, resulted in the following consumption distribution in the secondary treatment: air-process = 83% of the total consumption, SAB washings = 17%.…”
Section: (E) Energy Consumptionmentioning
confidence: 99%
“…The headloss increase recorded in the prototype bed was however slower than that recorded in continuous conventional biofilters [11], where washing operations are usually carried out every 1-2 days causing an excess sludge production as high as 0.5-0.6 kg TSS/kg COD removed [12,13]. On the contrary, as shown in Fig.…”
Section: Cod and Tss Removal Efficiency (%)mentioning
confidence: 73%